A prospective study on the effectiveness of a combination regime (Mifepristone and Misoprostol) in comparison with Misoprostol for missed abortion - Nidhi Gupta; Reva Tripathi; Sumedha Sharma; Aruna Nigam; Sanjeet Panesar (Journal of Family Medicine and Primary Care)
Introduction: Misoprostol is widely used in the medical management of missed abortions. However, pretreatment with Mifepristone has shown to be effective but still not recommended to be used in missed abortions. Aims and Objectives: To compare the outcome of medically managed missed abortion or blighted ovum using combination regime (Mifepristone and Misoprostol) vs Misoprostol alone. Materials and Methods: It was a prospective single-centre study performed in the Department of Obstetrics and Gynaecology, HIMSR and HAHC hospital, New Delhi, over, for one year. All the patients with diagnosed missed abortions were randomized into two groups (Group A and Group B). Group A was given Mifepristone 200 mg orally followed by Misoprostol 800 microgram per vaginal. Group B was given Misoprostol 800 microgram per vaginal. All the patients were observed for 24 hours for the expulsion of products of conception following the given regime. Ethical approval was taken from the Institutional Ethical Committee. Results: Both groups were comparable in demographic characteristics. On applying Fisher’s exact test, it has been observed that the odds of nonexpulsion of the product of conception, time taken in expulsion, and surgical evacuation because of excessive bleeding were significantly higher in Group B (Misoprostol) compared with Group A (Mifepristone followed by Misoprostol). The cost-effective analysis showed that the cost is higher among Misoprostol Group B compared with combination drugs of Group A (Mifepristone + Misoprostol), but this result is not significant. Conclusion: Mifepristone can be considered before Misoprostol in missed abortions. This regime might decrease the need for surgical evacuation.